Design and fluid flow simulation of modified laparoscopic forceps. Issue 8 (11th June 2021) - Junaidi, Md. Abdul Raheem; Kalluri, Ram Chandra Murthy; Rao, Y. V. Daseswara; Gokhale, Alla Gopala Krishna; Patel, Aakrit
Abstract: Laparoscopic surgery has gained prominence in recent decades and employed in minimally invasive surgeries to avoid massive cuts resulting in a reduction in pain, the chance of infection, and duration of stay in the hospital. Maryland forceps, which belongs to the category of grasper instruments, are often used in minimally invasive surgeries to hold, pull, push, manipulate, and perform dissection operations. During laparoscopic surgeries, often blood and other body fluids ooze from the site of surgery. Typically, suction–irrigation (SI) devices are used to periodically clear these fluids to get a better view of the site of surgery. To achieve this, the removal and insertion of multiple instruments are required. This process has to be repeated numerous times, which significantly increases the time needed for surgery. Literature survey and feedback from practicing surgeons suggest that this can be avoided by improving the current design of forceps. In this article, a modified design is proposed by combining the SI feature with the existing form of Maryland forceps. The modified design is first modeled in SolidWorks and then analyzed for fluid flow using ANSYS Fluent. Parametric analysis is performed to obtain the optimal design for the proposed multi-functional instrument, which can potentially improve the overall efficiency of the laparoscopic surgical process.